2021
DOI: 10.1002/advs.202003993
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Ferroelectric Characterization with Heterodyne Megasonic Piezoresponse Force Microscopy

Abstract: Piezoresponse force microscopy (PFM), as a powerful nanoscale characterization technique, has been extensively utilized to elucidate diverse underlying physics of ferroelectricity. However, intensive studies of conventional PFM have revealed a growing number of concerns and limitations which are largely challenging its validity and applications. In this study, an advanced PFM technique is reported, namely heterodyne megasonic piezoresponse force microscopy (HM-PFM), which uses 10 6 to 10 8 Hz high-frequency ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 162 publications
(402 reference statements)
4
22
0
Order By: Relevance
“…According to the histogram distribution analysis of IDS-PFM amplitude (as shown in Figure S8), the mean amplitude of this region is ∼1.23 pm; given the driven amplitude of 2 V, we are able to put an upper limit of ∼0.6 pm/V on the out of plane electromechanical response even if this sample exhibit ferroelectricity. Noteworthily, heterodyne megasonic PFM also indicates that the electromechanical response of CH 3 NH 3 PbI 3 is much smaller than quartz (2.3 pm/V), which is consistent with our results here.…”
Section: Resultssupporting
confidence: 92%
“…According to the histogram distribution analysis of IDS-PFM amplitude (as shown in Figure S8), the mean amplitude of this region is ∼1.23 pm; given the driven amplitude of 2 V, we are able to put an upper limit of ∼0.6 pm/V on the out of plane electromechanical response even if this sample exhibit ferroelectricity. Noteworthily, heterodyne megasonic PFM also indicates that the electromechanical response of CH 3 NH 3 PbI 3 is much smaller than quartz (2.3 pm/V), which is consistent with our results here.…”
Section: Resultssupporting
confidence: 92%
“…Recently, the inception of Heterodyne Megasonic PFM (HM‐PFM) provides a different way to measure the electrostrain by using the heterodyne detection method. [ 66,67 ] In HM‐PFM, the frequencies of the target electrostrain signal and the sample's AC drive are largely different, which tactfully makes the co‐frequency interferences in conventional PFM, for example, the electrostatic force, can be minimized significantly. Based on this design, the above‐mentioned co‐frequency interferences in QTF system, including the capacitance cross‐talk and parasitic oscillation, can also be avoided if a heterodyne detection scheme is adopted.…”
Section: Resultsmentioning
confidence: 99%
“…This fascinating selectable ferroic property is believed to play a key role in the efficient separation of lightactivated electron-hole pairs, 59,73 which is important to photoelectric conventions and has attracted considerable research interest. Various theoretical methods, such as DFT [59][60][61] and molecular dynamics (MD) simulations, 87,88 and experimental approaches, such as X-ray diffraction (XRD), 38,51,70,89 optical SHG, 53,70 scanning tunneling microscopy (STM), 90 and microscopic PFM, 25,55,57,[91][92][93][94][95][96][97] have been applied to investigate the ferroic structures and identify the ferroelectric and anti-ferroelectric behaviors of MAPbI 3 and other OMH perovskites, as shown in Table 1. In MAPbI 3 perovskite, the tetragonal phase with polarity is characterized and theoretically predicted to be in the I4cm space group with ferroelectricity.…”
Section: Ferroic Domain In Tetragonal Phasesmentioning
confidence: 99%
“…In the early stage, many researchers attributed the hysteresis behaviors of MAPbI 3 perovskite in the current-voltage (I-V) [46][47][48] and polarization-electric (P-E) 48,49 curves to the presence of ferroelectric domains; however, Beilsten-Edmands et al found that the nature of the hysteresis behavior originates from ionic migration. 50 Recently, evidence of ferroelectricity for MAPbI 3 perovskite with the I4 cm space group emerged from X-ray and neutron diffraction, 49,51,52 optical second harmonic generation (SHG) 53 and microscopic piezoresponse force microscopy (PFM) [54][55][56][57] studies. In addition to experimental evidence, theoretical works also verified the ferroelectricity in MAPbI 3 perovskite and were used to estimate the ferroelectric polarization.…”
Section: Introductionmentioning
confidence: 99%